2009
DOI: 10.2139/ssrn.1503350
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Accuracy of Different Market Structures - Bookmakers Versus a Betting Exchange

Abstract: There is a well-established literature on separately testing the prediction power of different betting market settings. This paper provides an inter-market comparison of the forecasting accuracy between bookmakers and a major betting exchange. Employing a dataset covering all football matches played in the major leagues of the "Big Five" (England, France, Germany, Italy, Spain) during three seasons (5478 games in total), we find evidence that the betting exchange provides more accurate predictions of the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…A strong positive relationship exists between the market odds and the likelihood of winning . Betting exchange markets are regarded as the most efficient financial betting market . Ignoring the social stigma attached to horse race gambling, the market provides a subjective probability of winning, and could highlight horses performing below their anticipated performance.…”
Section: Discussionmentioning
confidence: 99%
“…A strong positive relationship exists between the market odds and the likelihood of winning . Betting exchange markets are regarded as the most efficient financial betting market . Ignoring the social stigma attached to horse race gambling, the market provides a subjective probability of winning, and could highlight horses performing below their anticipated performance.…”
Section: Discussionmentioning
confidence: 99%
“…, ; Franck et al . ), we find that the odds at the bookmaker market are less efficient than those at the bet exchange market. Moreover, we show that bookmakers are willing to accept negative margins by posting more favourable odds than the rival bet exchange market, even though price transparency is high.…”
Section: Resultsmentioning
confidence: 58%
“…() and Franck et al . () . Thus inter‐market arbitrage opportunities emerge as a result of the different informational efficiency of the offered odds at the two betting markets.…”
Section: Inter‐market Price Differences and Informational Efficiencymentioning
confidence: 97%
See 1 more Smart Citation
“…The impact on prices due to organizational differences between betting markets is in no way trivial. Indeed, empirical evidence has shown that betting exchange odds are better than bookmakers' odds at predicting future events (Franck et al 2010). Put another way, price-setting errors are less common in betting exchanges, although various studies have shown that they are not entirely free of price-setting biases (Abinzano et al 2014(Abinzano et al , 2016).…”
mentioning
confidence: 99%